2000
DOI: 10.1007/s11926-000-0036-4
|View full text |Cite
|
Sign up to set email alerts
|

Vasculitis of the central nervous system

Abstract: Central nervous system (CNS) vasculitis occurs in a variety of clinical settings. Some exhibit a distinct age preference; others a tissue tropism. Most frequently encountered are giant cell arteritis (temporal arteritis) and vasculitis secondary to infections. The CNS may be involved in the systemic vasculitides, and neurologic abnormalities occasionally appear as a presenting manifestation of disease. Isolated angiitis of the CNS, a rare form of vasculitis restricted to the CNS, must be distinguished from oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…We did not perform a brain biopsy to exclude CNS vasculitis, but a "spontaneous" marked improvement in vascular stenoses would not be expected in this condition. 5 There was no evidence of a cardiac source of embolism. Urine toxicology screen was negative for drugs associated with vasoconstriction.…”
Section: Discussionmentioning
confidence: 95%
“…We did not perform a brain biopsy to exclude CNS vasculitis, but a "spontaneous" marked improvement in vascular stenoses would not be expected in this condition. 5 There was no evidence of a cardiac source of embolism. Urine toxicology screen was negative for drugs associated with vasoconstriction.…”
Section: Discussionmentioning
confidence: 95%
“…Glial nodules are nonspecific lesions that usually result from viral infection Prineas, MacDonald, and Franklin, 2002); in this case the nodules were negative by IHC for viruses, including SIV, and of unknown significance. Differential diagnoses for the occipital lobe lesion included a septic lesion of hematogenous origin (Kennedy, 2004;Moore, 2000), HSV encephalitis (Kennedy, 2004;Kennedy, 2005), and acute hemorrhagic leukoencephalitis (AHL). An extensive histopathologic workup failed to identify an infectious etiology, including HSV, as the cause of the vasculitis.…”
Section: Discussionmentioning
confidence: 99%
“…Nervous system Most SLE experts believe that the role of cerebral vessel vasculitis in the causation of central nervous system (CNS) lupus is overestimated, and that it is mostly caused by either a T cell-mediated or autoantibody-mediated damage to neuronal tissue [16][17][18]. In their original work, Johnson and Richardson [19] concluded that CNS involvement in SLE was due to vasculopathy (microinfarcts or fibrinoid degenerative changes).…”
Section: Visceral Vasculitismentioning
confidence: 99%